2021
DOI: 10.1038/s41598-021-90125-6
|View full text |Cite
|
Sign up to set email alerts
|

Frailty transitions and cognitive function among South Korean older adults

Abstract: Frailty is considered a multidimensional geriatric syndrome, manifested by the accumulation of age-associated deficits. The consequences of frailty transitions are still understudied. This study evaluated the influence of frailty transitions on cognitive function in the older adult population. We used data derived from the Korean Longitudinal Study of Aging (KLoSA) (2008–2018) on older adults aged ≥ 65 years. Frailty was assessed using a validated Korean frailty measure known as the frailty instrument (FI), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
2
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
0
15
2
1
Order By: Relevance
“… 28 It indicating that frailty has become a common problem for the older adults. 29 The major reasons for this inconsistency in the present study compared with a previous study might be the geographical variations and differences in measurement tools. And the rapidly ageing population and those with chronic diseases may result in a significantly increased demand for LTC.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“… 28 It indicating that frailty has become a common problem for the older adults. 29 The major reasons for this inconsistency in the present study compared with a previous study might be the geographical variations and differences in measurement tools. And the rapidly ageing population and those with chronic diseases may result in a significantly increased demand for LTC.…”
Section: Discussioncontrasting
confidence: 81%
“…However, the prevalence of frailty among older adults living in communities in the Asia-Pacific region is about 3.5%–27% 28. It indicating that frailty has become a common problem for the older adults 29. The major reasons for this inconsistency in the present study compared with a previous study might be the geographical variations and differences in measurement tools.…”
Section: Discussioncontrasting
confidence: 76%
“…Several studies in the literature have assessed the transitions in the frailty status, with separate times of observation and controversial results, not allowing to establish what is the best time to reassess it. 6 , 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…Also, as we assessed subject at 3 years, there may be transitions in frailty status that we are not capturing because of the time between visits. Several studies in the literature have assessed the transitions in the frailty status, with separate times of observation and controversial results, not allowing to establish what is the best time to reassess it 6,33,34 …”
Section: Discussionmentioning
confidence: 99%
“…The Morse Fall Scale score was also included in our nomogram. This score is often regarded as a significant indicator of frailty (34)(35)(36). Additionally, this study demonstrated that surgical time might independently predict the development of SSI in patients with gynecologic cancer, with 145 min serving as the cut-off value for categorization.…”
Section: Discussionmentioning
confidence: 71%